Effects of therapeutic exercise on the motor function of adults with Down syndrome (2023)
Therapeutic exercise exerts positive effects by mitigating or reducing the motor or cognitive changes that people with Down syndrome undergo throughout their life. There are no updated systematic reviews that integrate the evidence available in a way that facilitates decision-making for physical rehabilitation teams. This study therefore aimed to consolidate the information available and compare the effects of different types of physical exercise on the motor function of adults with DS. We conducted a systematic review and meta-analysis of randomized clinical trials and quasi-experimental studies. The literature search was performed between January 2023 and February 2023 using the PubMed, SCIELO, Epistemonikos, and Lilacs databases. Studies were selected according to pre-determined inclusion and exclusion criteria. The risk-of-bias assessment was performed using the risk-of-bias rating tool for randomized clinical trial (RoB) and the risk of bias of non-randomized comparative studies was assessed using the risk of bias in non-randomized studies of interventions (ROBINS-I) tool. Risk-of-bias assessment and meta-analyses were performed using the RevMan software package. Sixteen studies met the eligibility criteria for the qualitative synthesis and 4 were included in the meta-analyses. Combined exercise significantly increased muscle strength both in the upper limbs (SMD?=?0.74 [95% CI?0.25–1.22]) and lower limbs (SMD?=?0.56[95% CI?0.08–1.04]). Aerobic exercise improved spatiotemporal gait parameters. Aerobic exercise showed significant improvements in dynamic balance while combined exercise significantly increased dynamic and static balance. The certainty of the evidence was low to moderate for all outcomes. There was low and moderate certainty of evidence for the outcomes proposed in this review. However, therapeutic exercise could be effective in improving muscle strength and gait functionality.